Discovery of PXR Antagonist MI891 and PXR Degrader MI1013 and Their Roles in Hepatic Gene Regulation - Kamaraj, Rajamanikkam; Mejdrová, Ivana; Krutakova, Maria; Smutny, Tomas; Škach, Kryštof; Dohnalova, Klara; Smutna, Lucie; Nellore, Dharani Sai Sreekanth; Dusek, Jan; Chalupsky, Karel; Hricová, Jana; Kronenberger, Thales; et al. (Journal of medicinal chemistry, 2025)
The pregnane X receptor (PXR) is an important regulator of hepatic metabolism, yet mechanistic insights into the effects of pharmacological inhibition using PXR inverse agonists or antagonists on critical genes involved in both xenobiotic and endobiotic metabolism remain limited. Here, we discovered a novel PXR inverse agonist/antagonist, MI891, which binds to the ligand-binding domain of PXR. Furthermore, we computationally designed and synthesized the proteolysis-targeting chimera molecule, MI1013, based on the PXR antagonist SPA70, which degrades PXR in HepaRG hepatic cells. Using these tools, we investigated the regulation of key PXR target genes in HepaRG cells and human hepatocytes. Our findings indicate that PXR antagonism or degradation suppresses basal and rifampicin-induced expression of selected ADME genes. Moreover, the PXR antagonists and PROTAC degrader downregulate the expression of several key genes involved in gluconeogenesis, cholesterol homeostasis, bile acid synthesis, and proliferation in hepatocyte cells, suggesting their potential therapeutic applications for metabolic diseases.
Keywords: hepatocyty; Gene Expression Regulation; vztahy mezi strukturou a aktivitou; Drug Discovery; Hepatocytes; proliferace buněk; pregnanový X receptor; Liver; lidé; objevování léků; játra; Cell Proliferation; Humans; Pregnane X Receptor; Structure-Activity Relationship; regulace genové exprese